DEIKSIS PERSONA DALAM TUTURAN BAHASA BANJAR DI DESA STAGEN SUNGAI JUPI KECAMATAN PULAU LAUT UTARA KABUPATEN KOTABARU KALIMANTAN SELATAN - Sri Juniati; Rudy Suryana (STKIP Paris Barantai, 2018)
The aims of this research are 1) to describe the form of person deixis in language in Banjar in Sungai Jupi village, Pulau Laut Utara sub-district, Kotabaru district, South Kalimantan, 2) Describe the function of deixis persona in Banjar language in Sungai Jupi village, Pulau Laut Utara sub-district, Kotabaru district, South Kalimantan. The method used in this research is a qualitative method or naturalistic research method because the research is carried out in natural settings, also called qualitative methods because the data collected and the analysis are qualitative. This type of qualitative research is because the research data are verbal forms of language, namely in the form of speech deiksis persona in the Banjar language in the Jupi River Kotabaru Regency. The results of the study found several types of persona deixis in accordance with the content of the speaker. The forms of deixis of the persona are ulun, me, unda, pian, sidin, kam, inya, us, put in the ikam, and the content. The first person deixis includes, ulun, I, unda and us, the second person deixis includes pian, ikam, and ikam. the third person deixis includes sidin, inya, and bubuhannya Keywords: Deiksis Persona, Banjar Language Speech.